Effects of salts on oxidative stability of lipids in Tween-20 stabilized oil-in-water emulsions. (15th April 2016) - Cui, Leqi; Cho, Hyung Taek; McClements, D. Julian; Decker, Eric A.; Park, Yeonhwa
Highlights: NaCl promoted lipid oxidation of Tween-20 stabilized oil-in-water emulsions. Metal chelators DFO and EDTA were found to inhibit this effect. KCl produced similar lipid oxidation kinetics as NaCl in oil-in-water emulsions. Abstract: Lipid oxidation in oil-in-water (O/W) emulsions is an important factor determining the shelf life of food products. Salts are often present in many types of emulsion based food products. However, there is limited information on influence of salts on lipid oxidation in O/W emulsions. Thus, the purpose of this study was to examine the effects of sodium and potassium chloride on lipid oxidation in O/W emulsions. Tween 20 stabilized corn O/W emulsions at pH 7.0 were prepared with different concentrations of sodium chloride with or without the metal chelators. NaCl did not cause any changes in emulsion droplet size. NaCl dose-dependently promoted lipid oxidation as measured by the lipid oxidation product, hexanal. Both deferoxamine (DFO) and ethylenediaminetetraacetic acid (EDTA) reduced lipid oxidation in emulsions with NaCl, with EDTA being more effective. Potassium chloride showed similar impact on lipid oxidation as sodium chloride. These results suggest that salts are able to promote lipid oxidation in emulsions and this effect can be controlled by metal chelators.